Crystallographic Characterisation of Organolithium and Organomagnesium Intermediates in Reactions of Aldehydes and Ketones. Issue 9 (8th September 2022) - Lynch, Jennifer R.; Kennedy, Alan R.; Barker, Jim; Reid, Jacqueline; Mulvey, Robert E.
Abstract: We report reactions of LiNacNac and NacNacMg(TMP) with common organic substrates (TMP=2, 2, 6, 6‐tetramethylpiperidide). Using bulky β‐diketiminate compound NacNac (Me, Dipp), we have trapped metalated intermediates amenable to X‐ray crystallographic study. LiNacNac and acetone produced the NacNac‐free hexameric diacetone alkoxide [{LiO(MeC(=O)CH2 C(Me)2 }6 ]; whereas pinacolone gave the simple monomeric donor–acceptor complex [Li{(MeCN‐2, 6‐ i Pr2 C6 H3 )2 CH}{O=C(Me) t Bu}]. Benzaldehyde produced dimeric [Li{(MeCN‐2, 6‐ i Pr2 C6 H3 )2 CC(=O)Ph}{O=C(Ph)OCH2 Ph}]2, where one benzaldehyde molecule has inserted in to the γ‐carbon position of the NacNac ligand, with a molecule of benzyl benzoate derived from a Tishchenko reaction of the aldehyde acting as a terminal donor to lithium. Tetranuclear, mixed dimer [{LiO(MeCN‐2, 6‐ i Pr2 C6 H3 )2 CH‐CH(Ph)}2 {LiO(PhC(=O)}2 ] containing the same modified NacNac ligand was the fortuitous product from repeating the reaction of LiNacNac and benzaldehyde in a solution presumably contaminated with benzoic acid. Combining NacNacMg(TMP) with pinacolone affords monomeric heteroleptic [Mg{(MeCN‐2, 6‐ i Pr2 C6 H3 )2 CH}{OC( t Bu)(Me)CH2 C(=O) t Bu}] with an aldolate constituting the second anion. Completing the set is dimeric [Mg{(MeCN‐2, 6‐ i Pr2 C6 H3 )2 CH}{O(C=CH2 )Ph}2 ], where the enolate derived from acetophenone bridges the magnesium centres. Abstract :